Functional constraints on HIV-1 capsid: their impacts on the viral immune escape potency - Takemura, Taichiro; Murakami, Tsutomu (Frontiers in Microbiology, 2012)
In mature HIV-1 particles, viral capsid (CA) proteins form the conical core structure that encapsidates two copies of the viral RNA genome. After fusion of the viral envelope and cellular membranes, the CA core enters into the cytoplasm of the target cells. CA proteins then interact with a variety of viral other protein as well as host factors, which may either support or inhibit replication of the virus. Recent studies have revealed that CA proteins are important not only for the uncoating step but also for the later nuclear import step. Identification of proteins that interact with CA to fulfill these functions is, therefore, important for understanding the unknown HIV-1 replication machinery. CA proteins can also be targets of the host immune response. Notably, some HLA-restricted cytotoxic T-lymphocyte (CTL) responses that recognize CA functional regions can greatly contribute to delay in AIDS progression. The multi-functionality of the CA protein may limit the flexible virus evolution and reduce the possibility of an escape mutant arising. The presence of many functional regions in CA protein may make it a potential target for effective therapies.